Peran Five-Minute Meeting terhadap Target Output Bagian Sewing Line 34 di PT X - Widia Roker; Ary Kusmanto (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2026)
The internship program is part of the implementation of the Independent Learning and Independent Campus (MBKM) policy, which aims to provide students with real-world work experience. This internship report was prepared to analyze the role of the Five-Minute Meeting in achieving output targets for Sewing Line 34 at PT X. The internship was conducted in the Sewing section, where the student worked as a sewing operator. Data collection techniques included direct observation, interviews, documentation, and literature review during the internship. Observations showed that before the routine implementation of the Five-Minute Meeting, production output on line 34 was around 450 units per day, compared to the target of 500 units per day. After the consistent implementation of the Five-Minute Meeting, production output reached and even exceeded the company's target. Based on these results, it can be concluded that the Five-Minute Meeting plays a significant role in improving employee understanding of work targets, employee motivation, and achieving production output for the Sewing section, particularly on line 34, at PT X.